2020
DOI: 10.1128/mbio.00920-20
|View full text |Cite
|
Sign up to set email alerts
|

Host Fatty Acid Utilization by Staphylococcus aureus at the Infection Site

Abstract: Staphylococcus aureus utilizes the fatty acid (FA) kinase system to activate exogenous FAs for membrane synthesis. We developed a lipidomics workflow to determine the membrane phosphatidylglycerol (PG) molecular species synthesized by S. aureus at the thigh infection site. Wild-type S. aureus utilizes both host palmitate and oleate to acylate the 1 position of PG, and the 2 position is occupied by pentadecanoic acid arising from de novo biosynthesis. Inactivation of FakB2 eliminates the ability to assimilate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
46
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 50 publications
7
46
0
Order By: Relevance
“…The same group showed that exogenous fatty acids could occupy both the sn-1 and sn-2 positions of PG when cells were grown in brain heart infusion broth supplemented with C 14:0 , C 16:0 , and C 18:1 , or serum (38). This seemingly disproves the essentiality of the requirement for biosynthesized fatty acid anteiso C 15:0 at the sn-2 position (15,36,40) and undermines the viability of inhibitors of the FASII pathway as useful therapeutic agents (38). In this work, we also observed lipid species containing no C 15:0 , such as PG 32:1 (18:1/14:0), PG 34:1 (18:1/16:0 and 20:1/14:0), and PG 36:1 (18:1/18:0, 20:1/16:0, and 22:1/14:0), which supports the notion that anteiso C 15:0 is not essential.…”
Section: Discussionmentioning
confidence: 99%
“…The same group showed that exogenous fatty acids could occupy both the sn-1 and sn-2 positions of PG when cells were grown in brain heart infusion broth supplemented with C 14:0 , C 16:0 , and C 18:1 , or serum (38). This seemingly disproves the essentiality of the requirement for biosynthesized fatty acid anteiso C 15:0 at the sn-2 position (15,36,40) and undermines the viability of inhibitors of the FASII pathway as useful therapeutic agents (38). In this work, we also observed lipid species containing no C 15:0 , such as PG 32:1 (18:1/14:0), PG 34:1 (18:1/16:0 and 20:1/14:0), and PG 36:1 (18:1/18:0, 20:1/16:0, and 22:1/14:0), which supports the notion that anteiso C 15:0 is not essential.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus synthesizes or scavenges essential nutrients and evades immune responses to promote persistence during infection [1][2][3][4][5]. One such nutrient is fatty acids [6][7][8][9][10][11]. Fatty acids are essential to the structure and function of bacterial phospholipids and lipoproteins and serve to maintain membrane homeostasis [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporation of eFA from the host environment can support bacterial survival in the presence of FASII inhibitors through bypass of de novo fatty acid synthesis [12,19,25,26]. In addition, studies with human serum and murine thigh infection imply a degree of UFA incorporation by S. aureus even in the absence of FASII inhibitors [8,9]. Beyond restoring viability during FASII inhibition, the functional consequences of flexibility in membrane fatty acid composition on the virulence of S. aureus is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…PG 34:3 (16:1 + 18:2) is an unusual species, not commonly found in mammalian cells (LipidMAPS database), nor in A. baumannii grown in LB media (Fig 1i) (10). Hence, its presence in A. baumannii isolated from the mouse pleural cavity is a strong indicator of A. baumannii 18:2 acquisition from the host, reminiscent of 18:1 acquisition by S. aureus in mouse thigh tissue (11).…”
Section: Observationmentioning
confidence: 93%
“…PG 34:3 (16:1 + 18:2) is an unusual species, not commonly found in mammalian cells (LipidMAPS database), nor in A. baumannii grown in LB media ( Fig 1i ) (10). Hence, its presence in A. baumannii isolated from the mouse pleural cavity is a strong indicator of A. baumannii 18:2 acquisition from the host, reminiscent of 18:1 acquisition by S. aureus in mouse thigh tissue (11). The enhanced incorporation of 18:2 fatty acids in the A. baumannii PE and PG pools affected the total number of unsaturated fatty acids in A. baumannii from the PL, as compared to those cultured in LB, by 1.3-fold (PE) and 1.1-fold (PG) ( Fig 1k ).…”
Section: Observationmentioning
confidence: 99%